Sermons translated from the original French of the late Rev. James Saurin, pastor of the French church at the Hague - Saurin, Jacques (Printed by R. Edwards for Lackington, Allen, and Co., 1812)
v. 1. On the attributes of God -- v. 2. On the truth of revelation -- v. 3. On the principal doctrines of Christianity -- v. 4. On Christian morality -- v. 5. On various subjects -- v. 6. On sacramental occasions -- v. 7. On important subjects.